Determinants of Self-Management Behavior in Individuals with Hypertension: A Cross-Sectional Analysis - Sinaga, Friska; Ari, Elizabeth; Triastuti, Lidwina (Griya Eka Sejahtera, 2025)
Background: Hypertension is a leading contributor to global morbidity and mortality, necessitating not only pharmacological management but also effective self-management practices by patients. Identifying the factors influencing self-management behavior among hypertensive patients is essential for developing targeted interventions to improve health outcomes.Methods: This study employed a quantitative descriptive correlational design. A total of 105 hypertensive patients residing in the Saguling sub-district were selected using accidental sampling. Data collection instruments included a demographic questionnaire and the validated Hypertension Self-Management Behavior Questionnaire (HSMBQ). Data were analyzed using univariate and bivariate statistical methods, including Kendall’s Tau and Chi-square tests, with a significance level set at p < 0.05.Results: The findings revealed that various demographic factors—including age, education level, occupation, and duration of hypertension—were significantly associated with self-management behaviors. Most respondents demonstrated moderate levels of self-management. The study identified perceived barriers, self-efficacy, and social support as crucial factors affecting the patients’ ability to manage hypertension effectively.Conclusion: Understanding the demographic and psychosocial factors influencing self-management behaviors in hypertensive patients is vital for the development of effective health education and intervention programs. Strategies aimed at reducing perceived barriers and enhancing support systems could significantly improve hypertension outcomes.